1986
DOI: 10.1677/joe.0.1110043
|View full text |Cite
|
Sign up to set email alerts
|

Effects of constant infusion of gonadotrophin-releasing hormone in ovariectomized ewes with hypothalamo-pituitary disconnection: further evidence for differential control of LH and FSH secretion and the lack of a priming effect

Abstract: Experiments were conducted in ovariectomized ewes after hypothalamo-pituitary disconnection (HPD) to examine LH and FSH secretion during constant infusion of gonadotrophin-releasing hormone (GnRH) or physiological saline and to determine whether or not a constant GnRH background enhances or diminishes pituitary responsiveness to GnRH pulses. Whereas pulsatile GnRH infusions maintained LH and FSH secretion, constant infusions (125 or 250 ng/h) led to the complete cessation of LH secretion and reduced FSH secret… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
23
0

Year Published

1987
1987
2022
2022

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(27 citation statements)
references
References 20 publications
4
23
0
Order By: Relevance
“…This emerging hypothesis is supported by results of the in situ hybridization studies of Adams et al [I] describing similar GnRH messenger RNA levels in GnRH neurons from the hypothalamus of prepu bertal and adult monkeys, and by the recent report of this laboratory of comparable hypothalamic GnRH content at these two stages of development [4], Also consistent with the notion of unhindered GnRH synthesis by the hypo thalamus of the prepubertal monkey is the present finding that each injection of NMA. including the first, appeared to elicit an 'adult like' response from the network of GnRH neurons.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…This emerging hypothesis is supported by results of the in situ hybridization studies of Adams et al [I] describing similar GnRH messenger RNA levels in GnRH neurons from the hypothalamus of prepu bertal and adult monkeys, and by the recent report of this laboratory of comparable hypothalamic GnRH content at these two stages of development [4], Also consistent with the notion of unhindered GnRH synthesis by the hypo thalamus of the prepubertal monkey is the present finding that each injection of NMA. including the first, appeared to elicit an 'adult like' response from the network of GnRH neurons.…”
Section: Discussionsupporting
confidence: 87%
“…Here it should be noted that the idea of the hypo thalamus of the prepubertal monkey delivering a small, continuous flux of releasing factor to the gonadotrophs is not necessarily incompatible with earlier findings that ad ministration of pulsatile GnRH infusions stimulate LH se cretion during this phase of development [7,20]. In this re gard, Clarke et al (4] have recently demonstrated that in hypothalamic-pituitary-disconnected ewes pituitary responsiveness to GnRH pulses is not impaired by lowdose continuous GnRH infusions.…”
Section: Discussionmentioning
confidence: 67%
“…This is important because the gonadotropes normally function in response to pulsatile GnRH input from the hypothalamus, via the hypothalamo-hypophyseal portal system. Without such pulsatile GnRH input, LH secretion ceases (26), and constant GnRH input does not support secretion (33). On the other hand, FSH secretion is not as rigidly linked to pulsatile input of GnRH (34,35), and passive secretion may occur.…”
Section: Discussionmentioning
confidence: 99%
“…From previous studies in monkeys (19) and sheep (7) it has clearly been shown that pulsa$le GnRH treatment maintains the secretion of LH in animals deprived of endogenous GnRH but a constant infusion does not. Also from an earlier study, it was noted that since FSH continued to be secreted, albeit in diminishing amounts during constant infusion of GnRH, that pulsatile GnRH input may be necessary to maintain the synthesis but not the secretion of FSH (8). The maintenance of LHP and FSHP mRNA levels would appear to require pulsatile GnRH inputs since constant infusion of GnRH caused mRNA levels for both / 3 subunits to fall below those seen in OVX/HPD sheep given 250ng pulses of GnRH.…”
Section: Discussionmentioning
confidence: 96%
“…A temporal relationship has been demonstrated between secreted pulses of GnRH and LH (2), whereas FSH is not secreted in the same pulsatile fashion as LH (7). The two gonadotrophin hormones have been shown to be regulated differently by the steroid hormones, oestrogen and progesterone (4) and more recent studies have shown that pulsatile GnRH is necessary for secretion of LH, but not that of FSH (8); in addition, it has been shown that small pulses of GnRH do not permit LH secretion, whereas FSH secretion continues (9).…”
mentioning
confidence: 99%